Teachers Signs in the English Language Teaching Process - Melikuziyev Azimjon Latifjon ugli (Scientific Trends, 2025)
This article examines the use of gestures by teachers as an important methodological tool in the process of teaching English. The study was conducted among 30 English teachers working in secondary schools and universities in Tashkent. The article analyzes the role of gestures, in particular, such elements as hand gestures, facial expressions, eye contact, body movements and postures, in increasing students' interest in the lesson, understanding and motivation. It also discusses the differences in the cultural context of gestures and their role in distance learning. The results of the study confirm that the effective use of gestures in teaching English has a positive effect on the learning process.
Keywords: Gestures, pedagogical methods, intercultural communication, distance learning, facial expressions, body movements, hand gestures, motivation.